Factor-biased technical change and specialization patterns - Jana Brandt; Jürgen Meckl; Ivan Savin (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
We analyze the medium- and long-run effects of international integration of capital markets on specialization patterns of countries. For that purpose, we incorporate induced technical change into a Heckscher-Ohlin model with a continuum of final goods. This provides a comprehensive theory that explains the dynamics of comparative advantages based on differences in effective factor endowments. Our model constitutes an appropriate framework for understanding the changes in industrial structure of foreign trade observed, e.g., in the CEE countries over the last two decades. In addition, our approach provides a theoretical foundation for the empirical prospective comparative advantage index (Savin and Winker 2009) with new insights into the future dynamics of comparative advantages. Eventually, the model may serve as a basis to set development priorities in countries being in the period of transition.
Keywords: F15; F17; F21; F43; O33; 330; factor-biased technical change; continuum of goods; comparative advantage; factor mobility; innovation; knowledge spillovers; Faktorproportionentheorem; Technischer Fortschritt; Produktionsfaktor; Internationale Arbeitsteilung; Komparativer Kostenvorteil; Außenhandelsstruktur; Theorie; Ostmitteleuropa